A Monte Carlo-based Evaluation of Fishery Management Strategies for Lizardfish (Saurida undosquamis) in the Gulf of Suez, Red Sea (Global Journal of Science Frontier Research, 2023)
Abstract not found
Keywords: stock status; biological reference points; Saurida undosquamis; CMSY; Gulf of suez